(untitled) (Research, Society and Development, 2022)
Introduction: Dental caries and periodontal disease are the most common oral diseases in adolescents within the school population. In Brazil, little is known about the behavior and knowledge practices in oral health among school-age children. Objective: Thus, the objective of this study is to carry out a literature review with scientific evidence related to the importance of oral hygiene in children. Methodology: A qualitative review was chosen, whose data collection was carried out in October 2021. Results: results show that the school environment can choose, and also from literature, choose an environment. physical and mental health. Results and Discussions: Children from public schools were 3.8 times morem likely to have caries than more private schools; caries that assess determining factors for related oral health studies are considered to be key on the public oral health and management agenda, which plan interventions to promote oral health, very important. Conclusion: It is concluded that oral health education programs should be carried out school-wide on a large scale, and even parents should also be part of such educational programs.